Advances and challenges in identifying precursors of memory CD4+ T cells - Liu, Jianguo; Song, Wengang; Tang, Hua (Frontiers in Immunology, 2025)
Memory T (TM) cells play critical roles in protective immunity and immunopathology, and their generation and maintenance have attracted a lot of interests. In recent decades, informative investigations into CD8+ TM cell precursors have greatly enhanced our understanding of fate decision during CD8+ TM cell differentiation. Yet, much less is known about the generation of CD4+ TM cells and their precursors. In this review, we present advances in identifying precursors of CD4+ TM cells under Th1, Th2 and Th17 conditions, as well as current understanding of how intrinsic factors, extrinsic factors and positioning profiles contribute to determining fate choices of CD4+ T cells between effector and memory. However, the path toward a general theory of CD4+ TM cell generation has been hindered by technological limitations and diversity and plasticity of CD4+ T subsets at effector and memory phases. We thoroughly discuss the differences and similarities in differentiation of CD4+ TM cells under Th1, Th2, and Th17 conditions, and explore the prospects for identifying common precursors of specific CD4+ TM cells under various types of infections and exposures.